Fathoming fragile X in fruit flies. - Zhang, Y.Q.; Broadie, K. (Trends in Genetics, 2005)
Fragile X syndrome (FraX) is the most common inherited mental retardation disease. It is caused by mutation of the fragile X mental retardation 1 (fmr1) gene. The FMR1 protein (FMRP) is a widely expressed RNA-binding translational regulator with reportedly hundreds of potential targets. Recent work has focused on putative roles of FMRP in regulating the development and plasticity of neuronal synaptic connections. The newest animal model of FraX, the fruit fly Drosophila, has revealed several novel mechanistic insights into the disease. This review focuses on Drosophila FMRP as (i) a negative regulator of translation via noncoding RNA, including microRNA and adaptor BC1 RNA-mediated silencing mechanisms; (ii) a negative regulator of microtubule cytoskeleton stability; and (iii) a negative regulator of neuronal architectural complexity.